2020
DOI: 10.15283/ijsc20075
|View full text |Cite
|
Sign up to set email alerts
|

Intramyocardial Transplantation of Umbilical Cord Mesenchymal Stromal Cells in Chronic Ischemic Cardiomyopathy: A Controlled, Randomized Clinical Trial (HUC-HEART Trial)

Abstract: Background and Objectives: The HUC-HEART Trial (ClinicalTrials.gov Identifier: NCT02323477) was a controlled, prospective, phase I/II, multicenter, single-blind, three-arm randomized study of intramyocardial delivery of human umbilical cord-derived mesenchymal stromal cells (HUC-MSCs) combined with coronary artery bypass-grafting (CABG) in patients with chronic ischemic cardiomyopathy (CIC). The trial aimed to assess (i) the safety and the efficacy of cell transplantation during one-year follow-up, (ii) to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 30 publications
0
44
0
Order By: Relevance
“…MSCs, as promising cell candidates for transplantation, have been widely used in various clinical diseases especially ischemic heart diseases [ 15 ]. Recent clinical study demonstrated the safety of intramyocardial transplantation of HucMSCs in patients subjected to chronic ischemic cardiomyopathy by monitoring the incidence of adverse events within the 12 months follow-up period [ 16 ]. In the present study, we firstly evaluated the safety of HucMSCs in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MSCs, as promising cell candidates for transplantation, have been widely used in various clinical diseases especially ischemic heart diseases [ 15 ]. Recent clinical study demonstrated the safety of intramyocardial transplantation of HucMSCs in patients subjected to chronic ischemic cardiomyopathy by monitoring the incidence of adverse events within the 12 months follow-up period [ 16 ]. In the present study, we firstly evaluated the safety of HucMSCs in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Results from preclinical studies indicated the role of HucMSCs in improving the cardiac function in acute rat MI models [ 17 ]. Further randomized controlled trial suggested the significant efficacy of intramyocardial delivery of HucMSCs in chronic ischemic cardiomyopathy [ 16 ]. Consistent with these findings, intramyocardial administration of HucMSCs after MI can significantly improve LVEF and LVFS both on day 7 and 28, and further reduced LVEDV/LVESV and LVEDD/LVESD on day 28 in murine MI models.…”
Section: Discussionmentioning
confidence: 99%
“…The recently published phase I/II HUC-HEART Trial evaluated safety and efficacy of UC-MSC versus autologous BM-MSC combined with CABG in patients with chronic ischemic cardiomyopathy. After 12 months of follow-up, patients from the UC-MSC group showed an increase in left ventricular ejection fraction and a reduction in the necrotic myocardium area [ 127 ]. However, a similar randomized phase I trial using UC-MSC along with a collagen scaffold in chronic ischemic heart disease patients submitted to CABG have demonstrated that despite the absence of severe adverse effects, patients submitted to cell therapy along with the scaffold or not, had no significant change in fibrotic scar tissue [ 128 ].…”
Section: Msc-based Clinical Trials For Cardiomyopathy and Coronary Diseasementioning
confidence: 99%
“…Furthermore, UC-MSC-treated patients exhibit significant improvement in LVEF. In addition, the recently reported HUC-HEART trial compares the effects of UC-MSCs and BMMNCs in ICM patients [ 86 ]. UC-MSCs improve global cardiac function, stroke volume, and 6-min walk distance at 12-month follow-up.…”
Section: Msc Therapy In Clinical Trialsmentioning
confidence: 99%